Psychometric study of the brazilian version of the personality inventory for DSM-5–paper-and-pencil version - Barchi-Ferreira, Ana Maria; Osório, Flávia de Lima (Frontiers in Psychiatry, 2022)
The Personality Inventory for DSM-5 - Self Reported Form (PID-5-SRF) operationalizes Criterion B of the personality alternative model of DSM-5 Section III and has already been cross-culturally adapted to many countries. The objective is to present evidence of validity and reliability of the Brazilian version of PID-5 (pencil-and-paper) in a Brazilian community sample. The sample was composed of 730 individuals from the general population (67.8% women, aged 33.84 (SD=±15.2), 69.5% ≥12 years of schooling). The participants were recruited in academic, organizational, healthcare, and business facilities in three Brazilian states. The snowball method was used. The PID-5 Brazilian version and the Revised NEO-Five Factor Inventory (NEO-FFI-R) were individually applied, and the retest was applied 30 days after. Satisfactory internal consistency (facets α ≥0.51; domains α ≥0.82) and test-retest reliability (facets ICC ≥0.45; domains ICC ≥0.76) were found, but a floor effect was verified in 97.7% of the items. Regarding convergent validity, strong correlations were found between the PID-5 and the NEO-FFI-R domains (r= -0.44 to 0.70). Ten facets did not fit the unidemensional structure. Confirmatory Factor Analyses did not present adequate goodness of fit, and Exploratory Analyses indicated that a five-factor model is more appropriate, though it presents some peculiarities concerning the original model. PID-5 also presented satisfactory goodness of fit to the personality hierarchical model. Generally, the instrument’s psychometric indicators favor its use in the Brazilian context. However, some aspects demand attention, and more specific studies should be conducted to verify the impact of reverse-scored items, floor effect, and peculiarities of its internal structure (some facets’ multidimensionality and interstitiality) concerning the original model.